Effect of the Cognitive Conflict Strategy on the Performance of Some Offensive Situations for the Specialized School Football Players of Ages 14-16 - Ali fadhil Abaas; Rami Abdulameer Hassoon; Khalid Mohammed Ridha (Indian Journal of Forensic Medicine & Toxicology, 2021)
The importance of the research lies in preparing educational units with a strategy of cognitive conflict, andknowing the effect of educational units in the strategy of cognitive conflict in the performance of someoffensive positions for the players of the Specialized School of Football in Kerbala.As for the research problem, it was that the researchers noticed the difficulty of the development of playersin completing the correct offensive structure, due to the diversity of offensive positions, which makes theplayer unaware of the appropriate performance, with a weakness in the mental aspects of the player and hisinability to assemble an intellectual picture of the performance of the offensive duty optimally, and for thepurpose of using everything that would improve learning outcomes and achieve the desired benefit, movingfrom what he previously learned to what he is currently learning by using a modern knowledge strategyin the mathematical field that invests the learners’ abilities to the maximum extent possible, therefore, theresearchers decided to use this strategy and try to know its effect on the performance of some offensivesituations for football players.As for the objectives of the research, it was to identify the impact of the cognitive conflict strategy on theperformance of some offensive positions for the players of the specialized school of football at ages (14-16)years, as well as to identify the preference for the effect between the strategy of cognitive conflict and themethod used in the performance of some offensive positions in football at ages (14-16) years in the posttests.